Model Risk - an Agency Theoretic Approach - Friederike Schlegel; Hendrik Hakenes (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
In the recent financial crisis, risk management tools have been proven inadequate. Model risk, a key component of bank risk, has shown its negative impact. It seems that risk models did not cover the included risks comprehensively and were not kept up-to-date by banks, and also rating agencies. Consequently, in the aftermath of the crisis banks must adjust their models to reduce model risk. We discuss if banks undertake enough effort to improve their risk models. Furthermore, the paper deals with the optimal organizational structure of this improvement process. We take a close look at risk models of banks and discuss if banks generally invest enough effort to improve their risk models. The question of risk model innovation is analyzed from a managerial as well as from a welfare perspective in the context of a principal agent model - where the bank has to incentivize an agent to perform innovative improvement in the risk model technology.
Keywords: G01; G21; L22; 330